2019
DOI: 10.1111/apa.14889
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide epidemiology of early‐onset sepsis in Israel 2010‐2015, time to re‐evaluate empiric treatment

Abstract: Aim: Early-onset neonatal sepsis (EOS) may lead to significant morbidity and mortality, yet the recommended antimicrobials have not changed for many years. We aimed to optimise EOS treatment by examining EOS pathogens, resistance rates and resistance risk factors.Methods: A retrospective, nationwide cohort study analysing 2010-2015 EOS data in Israel. Results:The 21 participating centres constitute 92% of the total birth cohort (around 180 000 live births/year). Of 549 EOS neonates (0.57/1000 live births), 306… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
2
20
0
2
Order By: Relevance
“…In a single-center study conducted in Spain spanning the past 20 years, the incidence of neonatal E. coli early-onset sepsis was 0.69/ 1000 LBs [13]. In a study of 21 neonatal care centers in Israel from 2010 to 2015, the incidence of E. coli earlyonset infection was 0.2/1000 LBs [14]. In a study conducted at a tertiary hospital in India, the rate of neonatal sepsis with blood culture positivity was 6.2%, of which E. coli accounted for 14% [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a single-center study conducted in Spain spanning the past 20 years, the incidence of neonatal E. coli early-onset sepsis was 0.69/ 1000 LBs [13]. In a study of 21 neonatal care centers in Israel from 2010 to 2015, the incidence of E. coli earlyonset infection was 0.2/1000 LBs [14]. In a study conducted at a tertiary hospital in India, the rate of neonatal sepsis with blood culture positivity was 6.2%, of which E. coli accounted for 14% [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although progress has been made in the treatment of primary injuries after severe trauma, the incidence and mortality of posttraumatic sepsis have not been controlled well [ 1 4 ]. According to statistics, infection, second only to shock, is one of the main causes of sepsis and death after trauma, which can lead to multiple organ dysfunction syndrome (MODS) and even death in severe cases if not properly treated [ 3 , 5 7 ]. Early goal-directed therapy (EGDT) can improve the condition and prognosis of patients with sepsis, and clinical nursing is a key link to ensure the continuity of treatment, with an extremely important role.…”
Section: Introductionmentioning
confidence: 99%
“…However, an increase in the incidence of early-onset Escherichia coli sepsis has occurred during the same time period (4). Several studies have found that the incidence of early-onset E. coli sepsis has continued to increase over the last decades, and this has manifested itself as increased disease severity and risk of newborn death (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%